Tartaric acid modified Pleurotus ostreatus for enhanced removal of Cr(vi) ions from aqueous solution: characteristics and mechanisms. Issue 31 (8th April 2015) - Xu, Weihua; Wang, Shufan; Liu, Yunguo; Zeng, Guangming; Zheng, Bohong; Tan, XiaoFei; Li, Tingting; Wang, Hui; Guo, Fangying; Zhang, Mingming
<x xml:space="preserve">Abstract</x> Pleurotus ostreatus was modified by tartaric acid and used as a biosorbent for the removal of Cr(vi) from aqueous solution.